The lady says 'no' - Ross, Frank, 1904-1990; Niven, David, 1910-1983; Caulfield, Joan, 1922-1991; Ross-Stillman Productions Inc.; Cinetel Films ([West Hollywood, CA] : Ross-Stillman Productions Inc., 1952)
When a feminist author writes a fiery best-seller ripping into men, a debonair yet chauvinistic photographer arrives to do a feature on her for LIFE Magazine. But he has a hidden agenda: to prove her wrong and demonstrate that the male is still the superior sex! Sparks fly, but they eventually lead to romance in this charming, and very 1950s, comedy.
Joan Caulfield, David Niven, James Robertson Justice, Lenore Lonergan, Peggy Maley, Francis Bavier, Henry Jones.
Director of photography, James Wong Howe ; editor, Forge Amy; music, Arthur Lange & Emil Newman.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 9, 2015).
Keywords: Women authors -- Drama; Feminist drama; Man-woman relationships -- Drama; Feature films; Romantic comedy films; Fiction films; Internet videos; Streaming video